Perilaku Premature Sign Off atas Prosedur Audit Serta Kaitannya dengan Time Pressure dan Audit Risk - Arzal Syah; Muh. Abdi Imam; Hamida Hamida (JEMMA (Journal of Economic, Management and Accounting), 2021)
AbstractThe practice of premature sign off on audit procedures will directly affect the quality of the audit report produced by the auditor, because if one of the steps in the audit procedure is omitted, the possibility of the auditor making wrong judgments will be higher. This study aims to empirically prove the effect of time pressure and audit risk on premature sign off behavior on audit procedures. The population of this study is the auditor in the public accounting firm in Makassar City, Indonesia. Sample selection using census sampling technique. The results of this study indicate that time pressure tends to increase their efforts to prematurely terminate audit procedures (Premature sign Off). Auditors who perceive high audit risk tend to prematurely terminate audit procedures. When the auditor determines that the materiality inherent in the audit procedure is low, there is a tendency for the auditor to ignore the audit procedure because the auditor considers that if there is a material misstatement in the implementation of the audit procedure, the value is not material so that the auditor conducts premature sign off behavior.Keywords: Audit Risk, Premature Sign Off, and Time Pressure AbstrakPraktik premature sign off atas prosedur audit, akan berpengaruh secara langsung terhadap kualitas laporan audit yang dihasilkan oleh auditor, sebab apabila salah satu langkah dalam prosedur audit dihilangkan maka kemungkinan auditor dalam membuat judgment yang salah akan semakin tinggi. Penelitian ini bertujuan untuk membuktikan secara empiris pengaruh antara time pressure dan audit risk terhadap perilaku premature sign off atas prosedur audit. Populasi dari penelitian ini adalah auditor di kantor akuntan publik yang ada di Kota Makassar, Indonesia. Pemilihan sampel menggunakan teknik sampling sensus. Hasil dari penelitian ini menunjukkan bahwa time pressure, cenderung meningkatkan usahanya untuk melakukan penghentian secara prematur prosedur audit (Premature sign Off).  Auditor yang merasakan risiko audit yang tinggi cenderung untuk melakukan penghentian secara prematur prosedur audit.   Ketika auditor menetapkan bahwa materialitas yang melekat pada prosedur audit rendah maka terdapat kecenderungan auditor untuk mengabaikan prosedur audit dikarenakanan auditor menganggap jika terdapat salah saji material pada pelaksanaan prosedur audit nilainya tidaklah material sehingga auditor melakukan perilaku premature sign off.Kata Kunci: Audit Risk, Premature Sign Off, Time Pressure